Characterization of a Multicomponent Lithium Lithiate from a Combined X‐Ray Diffraction, NMR Spectroscopy, and Computational Approach1. Issue 48 (3rd October 2014) - Pöppler, Ann‐Christin; Granitzka, Markus; Herbst‐Irmer, Regine; Chen, Yu‐Sheng; Iversen, Bo B.; John, Michael; Mata, Ricardo A.; Stalke, Dietmar
Abstract An unusual lithium lithiate [Li(diglyme)2][(diglyme)Li2(C4H3S)3], made up from three carbanions, two lithium cations, and a single donor base molecule in the anion and a single lithium cation, coordinated by two donor base molecules, is investigated in a combined study including X‐ray diffraction, NMR spectroscopy and computational approaches in solution and the solid state. While the multicomponent lithiate is the only species present in the solid state, solution NMR spectroscopy and computational methods were employed to identify a second species in solution. The dimer [(diglyme)Li(C4H3S)]2 coexists with the lithiate in solution in a 1:1 ratio, the more the higher the polarity of the solvent is. Only the combination of this multitude of methods provides a firm picture of the whole.